Proportional and Integral Control in BLDC Motors - Bustanul Arifin; Dwi Susilo; Muhammad Shirotullah (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2026)
The implementation of BLDC (Brushless Direct Current) motors is very broad, both for the industrial world and for everyday household needs. This is because BLDC motor does not require brushes in its operation so it is more durable. This motor requires precise control to work optimally. This study aims to obtain conventional control so that it can be used properly. Based on the research, the BLDC motor could be modeled well in Matlab and has been tested through simulations. The test results showed that the developed model was able to represent the basic characteristics of the BLDC motor well and in accordance with theory. This modeling could be used as a reference in performance analysis and further development of BLDC motor control systems. PID control values ​​were obtained by increasing and decreasing control values. Based on the test, the parameter values ​​​​of Kp = 0.01 and Ki = 20 had successfully controlled the BLDC motor well. The system was able to respond to commands stably, steady-state errors could be minimized, and the motor speed could follow the desired reference value. This indicated that the control parameter settings used were effective enough to achieve BLDC motor control performance.